Preparation method and application of negative electrode carbon material for supercapacitor

The nitrogen and oxygen co-doped negative porous carbon materials prepared by hydrothermal synthesis and carbonization activation methods solve the problem of insufficient performance of the existing supercapacitor negative carbon materials, and achieve high specific capacitance and excellent electrochemical energy storage performance, which is suitable for high-performance supercapacitors.

CN119626791APending Publication Date: 2025-03-14YUNNAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411661453.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The negative carbon material of existing supercapacitors is insufficient, resulting in poor energy density, and excessive modification of functional groups will lead to slow electrochemical kinetics and poor rate performance.

Method used

Using hydrothermal synthesis and carbonization activation methods, carbon dots are generated through hydrothermal reaction of citric acid and urea, mixed with flour for gelatinization, followed by pre-carbonization and activation to obtain nitrogen and oxygen co-doped negative porous carbon materials with excellent structure and properties.

Benefits of technology

The prepared negative electrode carbon material has different specific surface areas and micropore distributions, showing excellent electrochemical energy storage performance. In 1M KOH electrolyte, when the current density is 20A/g, its specific capacitance can still be maintained at 390F/g, making it suitable for electrode materials for high-performance supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119626791A_ABST
    Figure CN119626791A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a negative electrode carbon material for a supercapacitor, and relates to the technical field of energy storage and electrode material preparation, and the preparation method comprises the following steps: dissolving citric acid and urea in ethanol, and sequentially carrying out magnetic stirring, hydrothermal treatment, purification and vacuum drying to obtain carbon dots; the preparation method comprises the following steps: dissolving carbon dots and flour in water, heating, gelatinizing and fully mixing while stirring, and then drying to obtain a precursor; and pre-carbonizing the precursor in a nitrogen atmosphere, taking out, grinding and mixing with alkali, activating in the nitrogen atmosphere, repeatedly washing with a diluted hydrochloric acid solution and water, and drying to obtain the negative electrode carbon material. The preparation method is simple in process, low in cost and suitable for large-scale industrial production, is used as a supercapacitor negative electrode material, shows excellent electrochemical energy storage performance, and has a wide application prospect in the field of preparation of cheap and high-performance supercapacitors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy storage and electrode material preparation, and in particular to a preparation method of a negative electrode carbon material for a supercapacitor and an application thereof. Background Art

[0002] With the continuous expansion of the market for portable electronic devices and electric vehicles, as well as the rapid development of solar power generation and wind power generation, energy storage devices that can meet different working conditions and environmental conditions have become a demand. Among them, supercapacitors with high power density, long cycle life and adaptability to harsh environmental conditions are increasingly valued. At present, supercapacitors have been widely used in small electronic devices, the automotive industry, grid stabilization systems, energy collection systems for wind turbines, etc. According to different energy storage mechanisms, researchers divide supercapacitors into two categories: double-layer supercapacitors and pseudocapacitors. Double-layer supercapacitors have faster charging rates and longer service life than pseudocapacitors, but due to their intrinsic energy storage mechanism, their specific capacity is lower than that of pseudocapacitors.

[0003] Carbon-based electrode materials are widely used as electrode materials for double-layer supercapacitors due to their high electrical conductivity, low cost, excellent chemical and thermal stability, adjustable structure, and environmental friendliness. However, the low specific capacity of carbon-based electrode materials leads to unsatisfactory energy density of assembled supercapacitors. To solve this problem, researchers have conducted in-depth research on two main strategies: introducing pseudocapacitive reactions and compounding with other conductive materials (such as graphene nanosheets). However, enhancing pseudocapacitance by modifying too many functional groups will lead to slow electrochemical kinetics and poor rate performance; secondly, due to its large size and poor compatibility, conductive nanocarbons cannot be fully combined with three-dimensional carbon at the molecular level to form an overall conductive network, resulting in limited performance improvement.

[0004] Carbon dots are used in the field of electrochemical energy storage due to their excellent electron transfer performance, low toxicity, chemical stability, and large specific surface area. Carbon dots have abundant edge sites, in-plane defects, abundant heteroatoms and functional groups, which enhance their hydrophilicity and pseudocapacitive activity. The quantum confinement effect given by their unique size greatly improves their electron migration rate. These characteristics enable them to be used as part of electrode materials and greatly improve the electrochemical performance of the overall material.

[0005] Therefore, in order to solve the above problems, this paper proposes a preparation method and application of negative electrode carbon material for supercapacitors. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a negative electrode carbon material for a supercapacitor, which solves the problem of insufficient performance of the negative electrode carbon material for a supercapacitor.

[0007] In order to achieve the above technical effects, the present invention is implemented by the following technical scheme: A method for preparing a negative electrode carbon material for a supercapacitor, characterized in that it comprises the following steps:

[0008] S1. Weigh citric acid and urea in a mass ratio of citric acid: urea = 1:1-4, dissolve the weighed citric acid and urea in a container filled with ethanol, and sequentially perform magnetic stirring, hydrothermal treatment, needle filter purification, and drying at 80-90° C. under vacuum conditions for 12 h to obtain carbon dots;

[0009] S2, weighing carbon dots and flour in a mass ratio of carbon dots to flour = 1:1-10, then dissolving the weighed carbon dots and flour in 10 ml of deionized water, heating at 50-70° C. while stirring to gelatinize for 10-50 min to ensure that the carbon dots and flour are fully mixed, and then drying at 80° C. for 12 hours to obtain a precursor;

[0010] S3, placing the precursor in a nitrogen atmosphere for pre-carbonization, taking it out, and obtaining a pre-carbonized product;

[0011] S4, weighing the pre-carbonized product and potassium hydroxide in a mass ratio of pre-carbonized product: potassium hydroxide = 1-5:1-5, and then grinding and mixing the weighed pre-carbonized product and potassium hydroxide to obtain a pre-product;

[0012] S5. Activate the pre-product under a nitrogen atmosphere, soak it in 1 mol / L dilute hydrochloric acid and stir it magnetically, use a suction filter to filter the hydrochloric acid solution, add 2 L of deionized water and filter it again, and then dry it at 70-100° C. for 12-24 hours to obtain the negative electrode carbon material for supercapacitors.

[0013] Furthermore, in S1, the usage ratio of ethanol to urea is 30 ml: 0.2-0.8 g.

[0014] Furthermore, in S1, the hydrothermal treatment is specifically: placing the container in an oil bath at 160-200° C. for heating for 10-14 hours.

[0015] Furthermore, in S1, the mass ratios of the carbon dots to the flour are 1:1, 1:1.5 and 1:2.

[0016] Furthermore, in S3, the pre-carbonization temperature is 400-600°C; the pre-carbonization process is specifically to keep the temperature for 1-2 hours after reaching the pre-carbonization temperature of 400-600°C.

[0017] Furthermore, in S4, the mass ratios of the pre-carbonized product to potassium hydroxide are 1:0.5, 1:1, 1:1.5 and 1:4.

[0018] Furthermore, in S5, the activation temperature is 600-800°C; the activation process is specifically to keep the temperature for 1-4 hours after reaching the activation temperature of 600-800°C.

[0019] Furthermore, the activation temperature is specifically 650°C, 700°C and 750°C.

[0020] Furthermore, in S5, the dilute hydrochloric acid solution is hydrochloric acid with a mass fraction of 2 to 5%.

[0021] Furthermore, the specific surface area of ​​the negative electrode carbon material for supercapacitor is 1 to 4000 m 2 / g, pore size distribution is 1.5~100nm.

[0022] Another object of the present invention is to provide an application of a negative electrode carbon material for a supercapacitor, characterized in that the negative electrode carbon material is used in the preparation of a supercapacitor.

[0023] The beneficial effects of the present invention are:

[0024] 1. The present invention adopts the method of hydrothermal synthesis and carbonization activation to prepare 2 / g) and micropore distribution (pore volume distribution in the range of 0.1 to 2 cm 3 / g) of nitrogen and oxygen co-doped negative electrode porous carbon material; the product has a simple production process, low cost, and is suitable for large-scale industrial production;

[0025] 2. The material prepared by the present invention mainly contains C, N, and O. Due to its excellent structure and performance, it is used as a supercapacitor electrode material. In a 1M KOH electrolyte, when the current density is 20A / g, its specific capacitance can still be maintained at 390F / g; the material exhibits excellent electrochemical energy storage performance and has broad application prospects in the field of preparing cheap, high-performance supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0027] Figure 1 TEM image of carbon dots in Example 1 of the present invention;

[0028] Figure 2 This is a scanning electron microscope image of the negative electrode carbon material in Example 1 of the present invention;

[0029] Figure 3 This is a transmission electron microscope image of the negative electrode carbon material in Example 1 of the present invention;

[0030] Figure 4 This is an X-ray photoelectron spectrum of the negative electrode carbon material in Example 1 of the present invention;

[0031] Figure 5 The isothermal adsorption curve and pore size distribution diagram of the negative electrode carbon material in Example 1 of the present invention;

[0032] Figure 6 The cyclic voltammetry curves of the electrochemical three-electrode system composed of the negative electrode carbon material in Example 1 of the present invention at different scan rates. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] The present invention provides a method for preparing a negative electrode carbon material for a supercapacitor, comprising the following steps:

[0036] (1) 0.192 g of citric acid, 0.384 g of urea and 30 ml of ethanol were added to a polytetrafluoroethylene reactor, and the solution was magnetically stirred for 10 minutes, followed by hydrothermal reaction at 180° C. for 12 hours; after the system was cooled to room temperature, the liquid in the reactor was filtered through a needle filter, and the filtrate was dried in a vacuum oven at 65° C. to obtain carbon dots; Figure 1 is a transmission electron microscope image of the carbon dots prepared in Example 1. Figure 1 It can be seen that the size of carbon dots is 5nm and the lattice fringes are 0.151nm.

[0037] (2) dispersing carbon dots and flour in 30 ml of deionized water, wherein the mass ratio of carbon dots to flour is 1:2; magnetically stirring the solution at 60° C. for 30 minutes to fully mix the flour and carbon dots by utilizing the gelatinization effect of the flour; and then drying at 85° C. for 12 hours to obtain a precursor;

[0038] (3) The precursor was placed in a tubular furnace, heated to 500°C at a rate of 2°C / min in a nitrogen atmosphere, and maintained for 1 hour to obtain pre-carbonized carbon; after the system was cooled to room temperature, the pre-carbonized carbon and potassium hydroxide were fully ground and mixed in a mass ratio of 1:4, and heated to 700°C at a rate of 3°C / min in a nitrogen atmosphere, and maintained for 2 hours to obtain activated carbon; then the potassium hydroxide in the sample was washed away with 3.65% by mass dilute hydrochloric acid, washed 5 times with deionized water, and dried at 80°C for 12 hours to obtain a negative electrode carbon material. Figure 2 is a scanning electron microscope image of the negative electrode carbon material prepared in Example 1. Figure 2 It can be seen that the material has a porous structure. Figure 3 is a transmission electron microscope image of the negative electrode carbon material prepared in Example 1. The black circle circles the outline of the composite carbon dots. Figure 3 It can be seen that the material has an amorphous structure and carbon dots are dispersed on the carbon skeleton.

[0039] (4) Take 5 mg of acetylene black in 5 ml of ethanol and ultrasonicate for 10 minutes, then add 18.75 mg of negative electrode carbon material and ultrasonicate for 5 minutes, finally add 25 μl of 5% PTFE emulsion and ultrasonicate for 5 minutes, heat and stir at 65°C until the liquid becomes a black paste to obtain an active slurry; select a nickel foam with a size of 1 cm × 9 cm as the current collector, and use chamfered glass to evenly coat the black paste on the carrier without obvious agglomeration or vacancies. The coating position is the front end of the carrier, and the coating area is a 1 cm × 1 cm square; the coated current collector is dried at 80°C for 12 hours to obtain a working electrode.

[0040] (5) Using 1 M potassium hydroxide solution as the electrolyte, mercury-mercury oxide electrode as the reference electrode, platinum sheet as the counter electrode, and then assembling the working electrode to form a three-electrode system, the negative electrode carbon material was tested using an electrochemical workstation.

[0041] Figure 4 is the X-ray photoelectron spectrum of the negative electrode carbon material prepared in Example 1. Figure 4 It can be seen that the composite material is rich in oxygen doping. Figure 5 The isothermal adsorption-desorption curve and pore size distribution diagram of the negative electrode carbon material prepared in Example 1 are obtained. The pore size distribution is calculated by the BJH method to obtain the following results: The specific surface area of ​​the negative electrode carbon material prepared in Example 1 is 3248.2677 m 2 / g, and the average pore diameter is 2.2867nm. Figure 6 is the cyclic voltammetry curve of the negative electrode carbon material prepared in Example 1 at different scan rates. Figure 6It can be seen that as the scan rate increases, the cyclic voltammetry curve remains rectangular, indicating that the composite electrode material has ideal capacitance and rate properties. Figure 7 is a charge and discharge curve diagram of the negative electrode carbon material prepared in Example 1 at different current densities. Figure 7 It can be seen that as the current density increases, the charge and discharge curve still presents a symmetrical triangle, indicating that the composite electrode material has ideal capacitance and rate properties.

[0042] Example 2

[0043] The present invention provides a method for preparing a negative electrode carbon material for a supercapacitor, comprising the following steps:

[0044] (1) 0.192 g of citric acid, 0.384 g of urea and 30 ml of ethanol were added to a polytetrafluoroethylene reactor, and the solution was magnetically stirred for 10 minutes, followed by hydrothermal reaction at 180° C. for 12 hours; after the system was cooled to room temperature, the liquid in the reactor was filtered through a needle filter, and the filtrate was dried in a vacuum oven at 65° C. to obtain carbon dots;

[0045] (2) dispersing carbon dots and flour in 30 ml of deionized water, wherein the mass ratio of carbon dots to flour is 1:1.5; magnetically stirring the solution at 60° C. for 30 minutes to fully mix the flour and carbon dots by utilizing the gelatinization effect of the flour; and then drying at 85° C. for 12 hours to obtain a precursor;

[0046] (3) The precursor was placed in a tubular furnace, heated to 500°C at a rate of 2°C / min in a nitrogen atmosphere, and maintained for 1 hour to obtain pre-carbonized carbon; after the system was cooled to room temperature, the pre-carbonized carbon and potassium hydroxide were fully ground and mixed in a mass ratio of 1:4, and heated to 650°C at a rate of 3°C / min in a nitrogen atmosphere, and maintained for 2 hours to obtain activated carbon; then the potassium hydroxide in the sample was washed away with 3.65% by mass dilute hydrochloric acid, washed 5 times with deionized water, and dried at 80°C for 12 hours to obtain a negative electrode carbon material.

[0047] Step (4) and step (5) are the same as in Example 1. A three-electrode test system is also prepared, and an electrochemical workstation is used to test the electrochemical properties of the negative electrode carbon material.

[0048] Example 3

[0049] The present invention provides a method for preparing a negative electrode carbon material for a supercapacitor, comprising the following steps:

[0050] (1) 0.192 g of citric acid, 0.384 g of urea and 30 ml of ethanol were added to a polytetrafluoroethylene reactor, and the solution was magnetically stirred for 10 minutes, followed by hydrothermal reaction at 180° C. for 12 hours; after the system was cooled to room temperature, the liquid in the reactor was filtered through a needle filter, and the filtrate was dried in a vacuum oven at 65° C. to obtain carbon dots;

[0051] (2) dispersing carbon dots and flour in 30 ml of deionized water, wherein the mass ratio of carbon dots to flour is 1:1; magnetically stirring the solution at 60° C. for 30 minutes to fully mix the flour and carbon dots by utilizing the gelatinization effect of the flour; and then drying at 85° C. for 12 hours to obtain a precursor;

[0052] (3) The precursor was placed in a tubular furnace, heated to 500°C at a rate of 2°C / min in a nitrogen atmosphere, and maintained for 1 hour to obtain pre-carbonized carbon; after the system was cooled to room temperature, the pre-carbonized carbon and potassium hydroxide were fully ground and mixed in a mass ratio of 1:4, and heated to 750°C at a rate of 3°C / min in a nitrogen atmosphere, and maintained for 2 hours to obtain activated carbon; then, the potassium hydroxide in the sample was washed away with 3.65% by mass dilute hydrochloric acid, washed 5 times with deionized water, and dried at 80°C for 12 hours to obtain a negative electrode carbon material.

[0053] Step (4) and step (5) are the same as in Example 1. A three-electrode test system is also prepared, and an electrochemical workstation is used to test the electrochemical properties of the negative electrode carbon material.

[0054] Example 4

[0055] The present invention provides a method for preparing a negative electrode carbon material for a supercapacitor, comprising the following steps:

[0056] (1) 0.192 g of citric acid, 0.384 g of urea and 30 ml of ethanol were added to a polytetrafluoroethylene reactor, and the solution was magnetically stirred for 10 minutes, followed by hydrothermal reaction at 180° C. for 12 hours; after the system was cooled to room temperature, the liquid in the reactor was filtered through a needle filter, and the filtrate was dried in a vacuum oven at 65° C. to obtain carbon dots;

[0057] (2) dispersing carbon dots and flour in 30 ml of deionized water, wherein the mass ratio of carbon dots to flour is 1:1; magnetically stirring the solution at 60° C. for 30 minutes to fully mix the flour and carbon dots by utilizing the gelatinization effect of the flour; and then drying at 85° C. for 12 hours to obtain a precursor;

[0058] (3) The precursor was placed in a tubular furnace, heated to 500°C at a rate of 2°C / min in a nitrogen atmosphere, and maintained for 1 hour to obtain pre-carbonized carbon; after the system was cooled to room temperature, the pre-carbonized carbon and potassium hydroxide were fully ground and mixed in a mass ratio of 1:0.5, and heated to 650°C at a rate of 3°C / min in a nitrogen atmosphere, and maintained for 2 hours to obtain activated carbon; then the potassium hydroxide in the sample was washed away with 3.65% by mass dilute hydrochloric acid, washed 5 times with deionized water, and dried at 80°C for 12 hours to obtain a negative electrode carbon material.

[0059] Step (4) and step (5) are the same as in Example 1. A three-electrode test system is also prepared, and an electrochemical workstation is used to test the electrochemical properties of the negative electrode carbon material.

[0060] Example 5

[0061] The present invention provides a method for preparing a negative electrode carbon material for a supercapacitor, comprising the following steps:

[0062] (1) 0.192 g of citric acid, 0.384 g of urea and 30 ml of ethanol were added to a polytetrafluoroethylene reactor, and the solution was magnetically stirred for 10 minutes, followed by hydrothermal reaction at 180° C. for 12 hours; after the system was cooled to room temperature, the liquid in the reactor was filtered through a needle filter, and the filtrate was dried in a vacuum oven at 65° C. to obtain carbon dots;

[0063] (2) dispersing carbon dots and flour in 30 ml of deionized water, wherein the mass ratio of carbon dots to flour is 1:1.5; magnetically stirring the solution at 60° C. for 30 minutes to fully mix the flour and carbon dots by utilizing the gelatinization effect of the flour; and then drying at 85° C. for 12 hours to obtain a precursor;

[0064] (3) The precursor was placed in a tubular furnace, heated to 500°C at a rate of 2°C / min in a nitrogen atmosphere, and maintained for 1 hour to obtain pre-carbonized carbon; after the system was cooled to room temperature, the pre-carbonized carbon and potassium hydroxide were fully ground and mixed in a mass ratio of 1:1, and heated to 700°C at a rate of 3°C / min in a nitrogen atmosphere, and maintained for 2 hours to obtain activated carbon; then, the potassium hydroxide in the sample was washed away with 3.65% by mass dilute hydrochloric acid, washed 5 times with deionized water, and dried at 80°C for 12 hours to obtain a negative electrode carbon material.

[0065] Step (4) and step (5) are the same as in Example 1. A three-electrode test system is also prepared, and an electrochemical workstation is used to test the electrochemical properties of the negative electrode carbon material.

[0066] Example 6

[0067] The present invention provides a method for preparing a negative electrode carbon material for a supercapacitor, comprising the following steps:

[0068] (1) 0.192 g of citric acid, 0.384 g of urea and 30 ml of ethanol were added to a polytetrafluoroethylene reactor, and the solution was magnetically stirred for 10 minutes, followed by hydrothermal reaction at 180° C. for 12 hours; after the system was cooled to room temperature, the liquid in the reactor was filtered through a needle filter, and the filtrate was dried in a vacuum oven at 65° C. to obtain carbon dots;

[0069] (2) dispersing carbon dots and flour in 30 ml of deionized water, wherein the mass ratio of carbon dots to flour is 1:2; magnetically stirring the solution at 60° C. for 30 minutes to fully mix the flour and carbon dots by utilizing the gelatinization effect of the flour; and then drying at 85° C. for 12 hours to obtain a precursor;

[0070] (3) The precursor was placed in a tubular furnace, heated to 500°C at a rate of 2°C / min in a nitrogen atmosphere, and maintained for 1 hour to obtain pre-carbonized carbon; after the system was cooled to room temperature, the pre-carbonized carbon and potassium hydroxide were fully ground and mixed in a mass ratio of 1:1.5, and heated to 750°C at a rate of 3°C / min in a nitrogen atmosphere, and maintained for 2 hours to obtain activated carbon; then, the potassium hydroxide in the sample was washed away with 3.65% by mass dilute hydrochloric acid, washed 5 times with deionized water, and dried at 80°C for 12 hours to obtain a negative electrode carbon material.

[0071] Step (4) and step (5) are the same as in Example 1. A three-electrode test system is also prepared, and an electrochemical workstation is used to test the electrochemical properties of the negative electrode carbon material.

[0072] Example 7

[0073] This embodiment summarizes and explains Embodiments 1-6;

[0074] A comparison table of sample preparation methods of the examples was established, as shown in Table 1:

[0075] Table 1

[0076]

[0077]

[0078] The electrochemical energy storage performance test comparison table of the samples in the embodiment at different current densities was established, as shown in Table 2:

[0079] Table 2

[0080] Example 5A / g 10A / g 20A / g 1 430F / g 403F / g 389F / g 2 387F / g 364F / g 353F / g 3 292F / g 275F / g 267F / g 4 281F / g 270F / g 262F / g 5 218F / g 210F / g 205F / g 6 250F / g 241F / g 235F / g

[0081] From Table 1, Table 2 and Figure 6It can be seen that under the conditions of different rates, the electrode sheet of the negative electrode carbon material prepared in Example 1 has the highest initial specific capacity and good rate performance, indicating that the negative electrode carbon material prepared in Example 1 shows the highest energy density in the capacitor and good capacity retention rate at high rate.

Claims

1. A method for preparing a negative electrode carbon material for a supercapacitor, characterized in that: It consists of the following steps: S1. Weigh citric acid and urea in a mass ratio of citric acid: urea = 1:1-4, dissolve the weighed citric acid and urea in a container filled with ethanol, and sequentially perform magnetic stirring, hydrothermal treatment, needle filter purification, and drying at 80-90° C. under vacuum conditions for 12 h to obtain carbon dots; S2, weighing carbon dots and flour in a mass ratio of carbon dots: flour = 1-10:1-10, then dissolving the weighed carbon dots and flour in 10 ml of deionized water, heating at 50-70° C. while stirring to gelatinize for 10-50 min to ensure that the carbon dots and flour are fully mixed, and then drying at 80° C. for 12 hours to obtain a precursor; S3, placing the precursor in a nitrogen atmosphere for pre-carbonization, taking it out, and obtaining a pre-carbonized product; S4, weighing the pre-carbonized product and potassium hydroxide in a mass ratio of pre-carbonized product: potassium hydroxide = 1-5:1-5, and then grinding and mixing the weighed pre-carbonized product and potassium hydroxide to obtain a pre-product; S5. Activate the pre-product under a nitrogen atmosphere, soak it in 1 mol / L dilute hydrochloric acid and stir it magnetically, use a suction filter to filter the hydrochloric acid solution, add 2 L of deionized water and filter it again, and then dry it at 70-100° C. for 12-24 hours to obtain the negative electrode carbon material for supercapacitors.

2. The method for preparing a negative electrode carbon material for a supercapacitor according to claim 1, characterized in that: In S1, the usage ratio of ethanol to urea is 30 ml: 0.2-0.8 g.

3. The method for preparing a negative electrode carbon material for a supercapacitor according to claim 1, characterized in that: In S1, the hydrothermal treatment is specifically: placing the container in an oil bath at 160-200° C. for heating for 10-14 hours.

4. The method for preparing a negative electrode carbon material for a supercapacitor according to claim 1, characterized in that: In S3, the pre-carbonization temperature is 400-600°C; the pre-carbonization process is specifically to keep the temperature for 1-2 hours after reaching the pre-carbonization temperature of 400-600°C.

5. The method for preparing a negative electrode carbon material for a supercapacitor according to claim 1, characterized in that: In S5, the activation temperature is 600-800°C; the activation process is specifically to keep the temperature for 1-4 hours after reaching the activation temperature of 600-800°C.

6. The method for preparing a negative electrode carbon material for a supercapacitor according to claim 1, characterized in that: In S5, the dilute hydrochloric acid solution is hydrochloric acid with a mass fraction of 2-5%.

7. The method for preparing a negative electrode carbon material for a supercapacitor according to claim 1, characterized in that: The specific surface area of ​​the negative electrode carbon material for supercapacitor is 1 to 4000 m 2 / g, pore size distribution is 1.5~100nm.

8. An application of a negative electrode carbon material for a supercapacitor, characterized in that: Application of the negative electrode carbon material in preparing a supercapacitor.